Probe reconstruction for holographic X‐ray imaging. (16th February 2017) - Hagemann, Johannes; Robisch, Anna-Lena; Osterhoff, Markus; Salditt, Tim
Abstract : A comparison of different schemes for probe characterization of an X‐ray nano‐probe in a near‐field imaging setting is presented. Abstract : In X‐ray holographic near‐field imaging the resolution and image quality depend sensitively on the beam. Artifacts are often encountered due to the strong focusing required to reach high resolution. Here, two schemes for reconstructing the complex‐valued and extended wavefront of X‐ray nano‐probes, primarily in the planes relevant for imaging ( i.e. focus, sample and detection plane), are presented and compared. Firstly, near‐field ptychography is used, based on scanning a test pattern laterally as well as longitudinally along the optical axis. Secondly, any test pattern is dispensed of and the wavefront reconstructed only from data recorded for different longitudinal translations of the detector. For this purpose, an optimized multi‐plane projection algorithm is presented, which can cope with the numerically very challenging setting of a divergent wavefront emanating from a hard X‐ray nanoprobe. The results of both schemes are in very good agreement. The probe retrieval can be used as a tool for optics alignment, in particular at X‐ray nanoprobe beamlines. Combining probe retrieval and object reconstruction is also shown to improve the image quality of holographic near‐field imaging.